Pain and Consolation in Ignatian Spirituality - López Hortelano, Eduard (Concilium, 2025)
In Ignatian spirituality, pain and comfort play a fundamental role in the spiritual process. Saint Ignacius of Loyola developed a deep focus on the experience of pain as an essential part of the road to union with God. Physical and emotional pain can serve as an opportunity for the examination and development of faith, guiding the soul towards a greater intimacy with the divine. This article illuminates these constitutive aspects through three sources: The Autobiography (the experiences of Ignatius of Loloya), the Spiritual Exercises (the experience of the exercitant), and the hermeneutic of the 20th century on consolation and desolation.